THE EFFECT OF “UP” MOVIE ON STUDENTS’ VOCABULARY AT MTSN PAREPARE - Umar, Fadhly Akbar; Ardiana; Mannong, Andi Bulkis Maghfirah (FKIP Unismuh Makassar, 2023)
Vocabulary is an important aspect of learning english and any languanges. Students use vocabulary in order to develop ideas, thoughts and feelings. For students, mastering vocabulary is difficult since pronouncing and understanding words is difficult, and this discourages them to learn, because students only remember the vocabulary taught that day, which will be forgetten the next day due to a lack of implementation. This research aimed to improve students’ vocabulary mastery at MTsN Parepare by using “Up” movie. The researcher used pre-experimental research where the data gained from the vocabulary test. The population of the research was the eight grade of MTsN Parepare in the academic year 2022/2023. The result presented that the mean score of students’ vocabulary mastery consisted pre-test and post-test in terms of Noun, Adjective and Verb was 73,50 which categorized as “Poor” while post-test was 90,50 which categorized as “Good”. It is indicated that the mean score of pre-test and post-test was increase 17 point. The t-test analysis presented that by applying 0.05 level of of significant with the degree of freedom 23 and p value (sig.2-tailed) was 0.000 indicates that there is a significant difference of the result of pre-test and post-test of the students. In other words, the result of the (sig.2-tailed) of the students’ post test is not greater than the level of significance (0.000<0.05).